Predicting Transition‐Metal/Benzenehexathiol Systems as Effective Cathodes of Li‐S batteries with Conjugate Conductivity and Synergetic Discharge. Issue 26 (8th July 2020) - Cui, Mengnan; Zhao, Xiaolin; Wang, Tiantian; Qiu, Wujie; Song, Erhong
Abstract: Though lithium‐sulfur (Li−S) batteries possess extremely high theoretical energy density (2600 Wh kg −1 ), its practical application is significantly hindered due to the shuttle effect of lithium polysulfides and poor electronic conductivity of cycling products. For this case, developing new type of cathodes with high electronic conductivity and appropriate adsorption energy is an important strategy to improve the Li−S battery performance. Herein, by using first‐principle calculations, we systematically investigate the two‐dimensional transition metal organic framework compounds TM‐BHT (TM=transition metal, BHT=benzenehexathiol) as the possible cathode candidates for Li−S batteries. Among the various TM‐BHT system, Co/Ni/Cu‐BHT are considered to be potential cathode materials for the excellent electronic conductivity, moderate adsorption energy and structural stability. In addition, it is found that the Co/Ni/Cu‐BHT can not only catalyze the decomposition reactions of S8 /Li2 Sn, but also synergistically discharge with sulfur materials. This work demonstrates an effective design pathway and provides solutions for developing high‐performance Li−S batteries. Abstract : Two‐dimensional transition‐metal/benzenehexathiol (TM‐BHT) have been systematically researched by using first principle calculations as cathode materials for Li−S batteries. It is found that the Co/Ni/Cu‐BHT can not only improve poor conductivity and alleviate the shuttle effect, but also catalyze Li2 Sn (n=1, 2, 4, 6, 8) decomposition and synergistically discharge with sulfur.